Genes enterotoxigênicos e linhagens com ação antagônica em Staphylococcus spp. Isolados de queijo de coalho - Moraes, Juliana de Oliveira (2014)
The genus Staphylococcus has been target of research in the assessment of capacity and bacteriocigênica related to the detection of genes encoding enterotoxins studies. Many strains of Staphylococcus spp are able to produce bacteriocin, as well as staphylococcal enterotoxins. The ingestion of food contaminated with these toxins is a major cause of food poisoning worldwide. Particularly, the farmhouse cheese made from raw milk, is under investigation as the possible presence of antagonistic substances against pathogens and the presence of genes encoding enterotoxins. This study evaluated the ability bacteriocigenic and toxin profiles of staphylococcal strains isolated from curd cheese produced from raw milk of the hinterland of Alagoas. One hundred and ten strains were subjected to the test on solid medium antagonism against Listeria monocytogenes. Those strains of Staphylococcus that showed antagonistic action will L. monocytogenes were evaluated for the ability bacteriocigenic against other pathogens (S.thyphimurium, P. aeruginosa, S. aureus and E. coli), the taxonomic identification through the commercial system API - Staph (BioMérieux®) and search enterotoxigenic classics genes (sea, seb, sec, sed e see) by PCR technique - Uniplex . Of the 110 strains of Staphylococcus spp evaluated, 34,5 % (38/110) showed antimicrobial activity against L. monocytogenes. Of these, none were able to inhibit E. coli and S. typhimurium, however, 42,1 % (16/38) showed inhibition against P. aeruginosa and 2,6 % (1/38) S. xylosus identified as presented antimicrobial activity against S. aureus. Strains with effect bacteriocigênico 9 (23,7%) belonged to group Staphylococcus coagulase positive (S. aureus ) and 29 (76,3 %) to S. coagulase negative group (S. lentus, S. haemolyticus, S. xylosus, S. simulans, S. sciuri, S. hominis). The largest number of strains with antimicrobial potential belonged to species S. haemolyticus. Among the tested strains, 60,5% (22/38) had at least one gene encoding staphylococcal enterotoxin classic, being 67,6% (6/9) Staphylococcus coagulase positive and 55,2% (16/29) Staphylococcus coagulase negative. The sea gene was detected in 50,0% (19/38) and the lines sec in 44,7% (17/38). The most frequent association was the sea and sea + sec e sea + seb + sec. The strains with antimicrobial activity against L. monocytogenes 42,1% (16/38) showed no enterotoxigenic classics genes. That there is a direct relationship between antagonist activity and the presence of genes encoding classical enterotoxins thus far. The results also showed high percentage of strains with enterotoxigenic potential Staphylococcus coagulase negative, which confronts the current Brazilian legislation, which favors only the count of coagulase positive for foods such as routine analysis and reveal that some strains of Staphylococcus have bioprotector character opposite L. monocytogenes, P. aeruginosa and S. aureus.